Analysis of the stiffness sensitivity of a sorting arm mechanism based on a generalized modal mass distributing matrix. (November 2018) - Jiang, Xuchu; Li, Bin; Liu, Hongqi; He, Songping; Mao, Xinyong; Jiang, Wei
A light-emitting diode chip sorting machine, which operates at high frequencies, exhibits reciprocating motion with multiple degrees of freedom and is characterized by quick starts and stops over a short range at a high frequency. The stiffness sensitivity of the chip sorter directly influences the positional accuracy of the sorting arm. However, existing experimental modal analysis methods cannot effectively identify the structural stiffness sensitivity under high-speed operation conditions. In this article, a method based on the modal mass distribution matrix is used to analyze the stiffness sensitivity of the sorting arm system. This method retrieves the modal parameters by modal analysis, after which the modal mass distribution matrix is obtained. The size of each element in the column of the matrix represents the energy distribution and stiffness sensitivity of the system under the mode. The stiffness-sensitive components of the sorting arm machine are accurately and quickly identified, thereby providing the guiding principle and basis for the dynamic optimization of the sorting arm mechanism.